Kesetaraan Gender dalam Memperoleh Pendidikan Islam Masa Klasik - Fahrur Rozy; Ibnu Alwi Jarkasih Hrp; Fatma Yulia (EduInovasi: Journal of Basic Educational Studies, 2024)
In the Arab jahiliyah tradition, it has long been known that girls or women are treated unfairly. This research aims to examine the role of women in obtaining and developing classical Islamic education. The method used is literature study. The results of this research are that classical Islamic education does not really matter about gender. In general, both men and women had equal access to education in kuttabs, palace schools, mosques and other classical educational institutions. The Prophet always gave equal rights to men and women, he taught education to all groups. Therefore, great educators and leaders emerged from among women, for example Aisyah, an expert in fiqh and tafsir, Siti Shafiyyah, a language expert, and Fatimah al-Fihri, the founder of the first university in the world.